Digital Transformation in Islamic Religious Education: Opportunities, Challenges, and Strategic Solutions - Ari Koswara; Darmanto; Indah Wigati; Suhadi (Sustainable, 2026)
The rapid advancement of digital technologies has fundamentally transformed educational practices, particularly in Islamic Religious Education (PAI), where technology integration must balance pedagogical innovation with moral and spiritual values. This study explores digital transformation in PAI learning by reviewing and synthesizing relevant scholarly literature published between 2020 and 2025. Drawing on peer-reviewed journal articles, conference proceedings, and academic publications sourced from Google Scholar and nationally accredited journals, the review focuses on themes of digital pedagogy, teacher competence, ethical considerations, and the application of the TPACK framework in value-based education. The synthesis highlights three key dimensions: (1) opportunities, where technology enhances learning accessibility, student engagement, and instructional personalization through interactive media and digital platforms; (2) challenges, including infrastructural limitations, varying levels of teacher digital competence, and ethical concerns regarding content authenticity and data privacy in religious contexts; and (3) strategic solutions, emphasizing continuous TPACK-based professional development, the creation of religiously aligned digital content, and supportive institutional policies. This review contributes a conceptual understanding of how digital transformation can be sustainably integrated into PAI, underscoring that successful implementation requires holistic alignment of technology, pedagogical competence, ethical governance, and systemic support. The findings offer practical recommendations for educators